Research Progress in the Prevention and Treatment of Diabetic Kidney Disease Using Traditional Chinese Medicine - Ren, Bo; Shi, Jian (Journal of Contemporary Medical Practice, 2025)
The pathogenesis of diabetic nephropathy is complex and falls under the categories of “kidney deficiency,” “lower deficiency,” and “edema” in traditional Chinese medicine. In recent years, significant progress has been made in the prevention and treatment of diabetic nephropathy using traditional Chinese medicine. Traditional Chinese medicine has extensive experience and treatment methods for this condition. This study reviews the application of herbal decoctions, compound formulas, and acupuncture and massage in the treatment of diabetic nephropathy. These treatment methods complement each other and yield significant therapeutic effects. However, more high-quality clinical trials and basic research are needed to clarify the optimal treatment protocols and target mechanisms of TCM, thereby promoting its further development in the prevention and treatment of diabetic kidney disease.